(untitled) (International Journal of Innovative Computing, 2024)
Mathematics is useful in everyday life particularly in solving problems. Teaching or having a good understanding in mathematics is challenging as students having different kinds of learning preferences including personalities, interests, learning abilities and needs. This study presents how an adaptive game-based learning can help in improving students’ learning mathematic experience while helping them develop an interest in learning mathematic subjects. Adaptive game-based learning provides entertainment and better engagement of the students in learning as most students love to play games during their free time. To evaluate the usefulness of adaptive game-based learning approach towards the students’ mathematic learning, an experimental study with 20 primary school students and 1 teacher from SJK(C) Pui Chi was conducted through an integrated application called ALearn. The finding shows most of the students gave positive feedback and agreed that the adaptive game-based learning approach is very helpful and useful in enhancing their learning particularly in mathematics subject.